The Undergraduate Students Critical Thinking in Writing Evaluative Annotated Bibliography in Extensive Reading Class (RETAIN, 2019)
Abstrak Setiap mahasiswa perlu memiliki kemampuan untuk berpikir kritis. Salah satu cara yang dapat dilakukan untuk mengamati dan mengembangkan kemampuan siswa dalam berpikir kritis ialah dengan menugasi mereka untuk menulis evaluative annotated bibliography. Oleh karena itu, penelitian ini bertujuan untuk menggambarkan bagaimana kemampuan berpikir kritis mahasiswa terefleksikan dalam tulisan evaluative annotated bibliography mereka, dan bagaimana kemampuan berpikir kritis digunakan dalam menulis evaluative annotated bibliography. Objek dari penelitian ini adalah 9 hasil tulisan evaluative annotated bibliography mahasiswa dan subjeknya ialah 29 mahasiswa di Kelas Extensive Reading A di UNESA. Terdapat dua instrumen utama yang digunakan peneliti untuk menjawab kedua rumusan masalah, yaitu hasil tulisan mahasiswa bersamaan dengan rubrik yang diadaptasi dari Mesa Community College bernama Summarize & Critically Analyze Paper Rubric dan kuesioner. Selebihnya, wawancara juga dilakukan oleh peneliti sebagai instrumen pelengkap yang bertujuan untuk melengkapi data yang diperoleh dari kuesioner untuk menjawab rumusan masalah kedua. Semua data dianalisis secara kualitatif dengan menerapkan tiga langkah penelitian kualitatif; yaitu, pengenalan & pengorganisasian, pengkodean & pengurangan, dan penafsiran & penggambaran. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis mahasiswa telah terefleksikan dalam tulisan evaluative annotated bibliography mereka, khususnya pada bagian ringkasan dan respon kritis. Selain itu, hasil juga menunjukkan bahwa mahasiswa tidak hanya menggunakan kemampuan berpikir kritis dalam mengembangkan evaluative annotation, namun juga dalam menemukan solusi yang tepat untuk menyelesaikan masalah yang mereka temui selama menulis evaluative annotated bibliography. Kata Kunci: berpikir kritis, evaluative annotated bibliography, kelas extensive reading Abstract As one of the most important educational goals, all students need to possess critical thinking skills. One of the ways to analyze and promote the students’ critical thinking is by assigning them to write Evaluative Annotated Bibliography. Thus, this present study is aimed at describing how the students critical thinking is reflected in their evaluative annotated bibliography and exploring how the students use critical thinking in constructing evaluative annotated bibliography. The objects of this study were 9 students evaluative annotated bibliography writing results and the subjects were the 29 students in Extensive Reading Class A in UNESA. There were two main instruments used by the researcher to answer two research questions. First, the students writing results along with the rubric namely Summarize & Critically Analyze Paper Rubric proposed by Mesa Community College, and the second is a questionnaire. Moreover, the unstructured format interview was also used as the complementary instrument to support the data obtained through the questionnaire to answer the second research question. In addition, the data were analyzed qualitatively by occupying the three stages; familiarizing & organizing, coding & reducing, and interpreting & representing. The results showed that the students critical thinking has been reflected in their evaluative annotated bibliography writing, specifically in their summary and critical response section. Moreover, it is also found that the students used critical thinking not only in developing their evaluative annotation but also in finding the appropriate solutions to overcome the problems they experienced while developing their writing. Keywords: critical thinking, evaluative annotated bibliography, Extensive Reading Class.